(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
The purpose of the studywas an assessment of the cognitive and psychoemotional sphere in patients with chronic cerebral ischemia